Trouble in the Middle. - Feldman, Steven P. (Taylor and Francis, 2013)
This book will help readers better understand the ethical and cultural assumptions that both American and Chinese business cultures bring to business relationships in China. It analyzes the relationships developed between the two cultures, areas where they conflict, and how these conflicts are (or are not) resolved. These relationships are investigated in three stages. The author:describes and interprets American business experience in China describes and interprets Chinese business experience in China, including interaction with Americanscompares these t.